2020
DOI: 10.3390/agronomy10081079
|View full text |Cite
|
Sign up to set email alerts
|

Phloroglucinol Improves Direct Rooting of In Vitro Cultured Apple Rootstocks M9 and M26

Abstract: Advances in micropropagation techniques have helped produce true-to-type clones of many horticulturally important plants. However, several cultivars of apple are difficult to root in vitro. In these cases, adventitious roots are induced together with undesirable formation of callus, which decrease the acclimatization rate of in vitro produced plantlets. In this study, two apple rootstocks, M9 and M26, were subjected to different concentrations of indole-3-butyric acid (IBA) to induce root formation. Although a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Moreover, De Klerk et al (2011) observed different effects of PG on rooting depending on the specific auxin applied. A positive rooting response using PG and IBA has been reported for several tree genera, including Diaspyros, Malus (Dobránszki and Teixeria da Silva, 2010), Jatropha (Daud et al, 2013), Juglans (Licea-Moreno et al, 2015) and apple rootstocks Ma and M26 (Kim et al, 2020). It has been reported that PG acts synergistically with auxin during the most sensitive phase of root initiation (Dobránszki and Teixeira da siva, 2010).…”
Section: Root Induction and Acclimatizationmentioning
confidence: 96%
“…Moreover, De Klerk et al (2011) observed different effects of PG on rooting depending on the specific auxin applied. A positive rooting response using PG and IBA has been reported for several tree genera, including Diaspyros, Malus (Dobránszki and Teixeria da Silva, 2010), Jatropha (Daud et al, 2013), Juglans (Licea-Moreno et al, 2015) and apple rootstocks Ma and M26 (Kim et al, 2020). It has been reported that PG acts synergistically with auxin during the most sensitive phase of root initiation (Dobránszki and Teixeira da siva, 2010).…”
Section: Root Induction and Acclimatizationmentioning
confidence: 96%
“…Regeneration of adventitious roots from shoots remains to be problematic for in vitro apple plantlet production (De Klerk et al, 2011;Kim et al, 2020a). Consequently, several attempts have been directed toward the choice and combination of growth regulators, root induction procedure, one-or multiple-step culturing, and treatment duration (De Klerk et al, 2011;Kim et al, 2020a;Souza et al, 2022).…”
Section: Introductionmentioning
confidence: 99%